2019
DOI: 10.1155/2019/4060426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health-Promoting Lifestyle Education Intervention on Health-Promoting Behaviors and Health Status of Postmenopausal Women: A Quasi-Experimental Study from Sri Lanka

Abstract: Health promotion through lifestyle education is an important measure to enhance health status of postmenopausal women (PMW). This study evaluated the effectiveness of health-promoting lifestyle education intervention (HPLEI) on adhering to health-promoting behaviors (HPB) and enhancing the health status in a group of Sri Lankan PMW. A quasi-experimental study was conducted with randomly selected, sociodemographic status matched, 72 PMW from two geographically separated areas in Galle District, Sri Lanka, alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…The mean (SD) age of the intervention and control groups was 54.6 (4.5) and 56.5 (3.4) years (p = 0:06), respectively. Age at menopause, time since menopause, and sociodemographic characteristics were not different between the intervention and control groups [18]. Knowledge, attitude, MENQOL, and overall QOL scores were not different between the intervention and control groups at the baseline (Evaluation 1) (p values are not shown in tables).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The mean (SD) age of the intervention and control groups was 54.6 (4.5) and 56.5 (3.4) years (p = 0:06), respectively. Age at menopause, time since menopause, and sociodemographic characteristics were not different between the intervention and control groups [18]. Knowledge, attitude, MENQOL, and overall QOL scores were not different between the intervention and control groups at the baseline (Evaluation 1) (p values are not shown in tables).…”
Section: Resultsmentioning
confidence: 87%
“…Further, health education programmes on health improvement and maintenance of PMW have shown successful improvements in overall QOL in many domains [5,19,[38][39][40][41]. Our previous publication also reported that HPLEI is an effective way to establish good living habits and general health status of PMW [18]. Therefore, study population, duration, and intensity of the programme would not be a matter if the programme showed beneficial and truthful effects as reported by many studies in similar nature [5, 13 26-41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations